Fuzzy-based Wi-Fi localisation with high accuracy using fingerprinting. (2018) - Ibrahim, Michael; Nabil, Tarek; Halawa, Hassan H.; ElSayed, Hany M.; Daoud, Ramez M.; Amer, Hassanein H.; Ismail, Mohamed; Wahish, Mostafa; Ibrahim, Mohamed
In this paper, a localisation system based on Wi-Fi fingerprinting and fuzzy data analysis is presented. Three localisation techniques were used, Euclidean distance, K-nearest neighbours (KNN), and weighted K-nearest neighbours (WKNN), to get three independent estimations of a user's location. Then fuzzy analysis is used to combine the three estimates to achieve highly-accurate localisation. Two experiments were conducted in order to test the proposed new technique and compare it to the traditional fingerprinting techniques present in the literature. The results of the experiments proved that the proposed technique outperforms the traditional techniques.